2021
DOI: 10.1080/21691401.2021.1899193
|View full text |Cite
|
Sign up to set email alerts
|

Facile green synthesis of silver nanoparticles using Mangifera indica seed aqueous extract and its antimicrobial, antioxidant and cytotoxic potential (3-in-1 system)

Abstract: A novel approach for the utilisation of fruit waste is attempted in the present investigation. Mangifera indica seed aqueous extract was utilised for green synthesis of silver nanoparticles (AgNPs). The phytoconstituents in the seed acted as reducing and stabilising agent for AgNP formation. UV-Vis, Zeta potential, FT-IR, XRD, TEM, SAED, EDX analysis were used to characterise the green synthesised AgNPs. UV-vis spectra showed characteristic spectra at 450 nm; XRD and SAED confirmed the crystalline nature while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 51 publications
4
36
0
Order By: Relevance
“…e as-prepared Ag-NPs have a face-centred cubic structure. At the same time, additional peaks connected with standard Ag peaks can be attributed to the presence of phytochemicals extracted from espesia populnea, which might get capped on the surface of NPs [23,24]. e width of the (111) Bragg's reflection was used to calculate the average size of the fabricated Ag-NPs by using the Debye-Scherer equation (2).…”
Section: Resultsmentioning
confidence: 99%
“…e as-prepared Ag-NPs have a face-centred cubic structure. At the same time, additional peaks connected with standard Ag peaks can be attributed to the presence of phytochemicals extracted from espesia populnea, which might get capped on the surface of NPs [23,24]. e width of the (111) Bragg's reflection was used to calculate the average size of the fabricated Ag-NPs by using the Debye-Scherer equation (2).…”
Section: Resultsmentioning
confidence: 99%
“…Morinda citrifolia was utilized to prepare spherical silver nanoparticles with an average size of 3 nm and used to evaluate bacterial activity toward S. aureus (ZOI = 9.81 mm) and E. coli (ZOI = 10.63 mm) [245]. In another work, round silver nanoparticles were derived from Mangifera indica aqueous seed extract and tested against B. cereus (ATCC11778), K. pneumonia (NMCIM2719), S. aureus (ATCC29737), P. aeruginosa (ATCC9027), C. rubrum (ATCC14898), E. coli (NCIM2931), S. typhimurium (ATCC23564), C. neoformans (ATCC34664), C. albicans (ATCC2091), and C. glabrata (NCIM3438) [246]. The formation of spherical nanoparticles with an average of 22 nm utilizing Annona squamosa L. was reported by Jose, Vimala, et al The biosynthesized silver nanoparticles showed excellent catalytic activity against degradation of Coomassie brilliant blue dye [247].…”
Section: Synthesis Of Silver Nanoparticles Using Leaf Extracts: (2019-2020)mentioning
confidence: 99%
“…Donga and Chanda [ 49 ] found that the cytotoxicity of SPAgNPs on Hela cell lines increased with SPAgNPs’ concentration dependence. Furthermore, Barabadi, et al [ 50 ] stated the cytotoxicity of AgNPs against cervical cancer cells.…”
Section: Resultsmentioning
confidence: 99%